A new species of the genus Melita (Amphipoda, Hadzioidea, Melitidae) from anchialine pool on the Cozumel Island, NE Caribbean Sea - Ortiz, Manuel; Winfield, Ignacio (Zootaxa, 2016)
A new species of genus Melita collected from anchialine pool (Cenote Aerolito) on Cozumel Island is described.  Distinctive characters of male of the new species include an accessory flagellum 4–articulate; palm of gnathopod 2 with long setae; urosomite 2 with two robust setae on right side, and one on left. Female of the new species differs by coxa 6 without lateral ridge at base of hook, and anteroventral angle without stridulating ridges on anteroventral process; gnathopods 1–2 covered with long setae on articles 5–6. The main morphological differences between males of Melita species recorded previously for the Gulf of Mexico and the Caribbean Sea and the new species are also given.